Menghadirkan Gamifikasi dalam Pembelajaran Bahasa Jerman untuk Pemula: Desain Aplikasi BRIX Berbasis Construct 3 - Ibrahim Asmorodina; Desti Nur Aini (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2025)
This study aims to describe the development process of the BRIX application based on the Construct 3 platform for German language learning with gamification integration. This research employs a research and development (R&D) approach with a descriptive qualitative method and utilizes the Waterfall development model, which consists of five stages: needs analysis, design and development, application development, verification, and application launch. The research data were obtained through observations during the needs analysis stage and questionnaires during the trial phase, involving students from SMAN 1 Bululawang as research subjects. The result of this study is the BRIX application product, which is a type of learning media in the form of a 2D platformer and role-playing game (RPG). The gamification elements integrated into BRIX are designed to encourage student motivation in the German language learning process, equipped with game features such as characters, points, scores, and exercises that focus on reading (lesen) and listening (hören) skills at the A1 GER level.